Soil structural attributes in relation to land use in Shiwaliks region of northwest India - CHHINA, LOVEDEEP KAUR; GUPTA, R. K.; KUKAL, S. S. (Journal of Soil and Water Conservation, 2020)
Intensive cultivation coupled with monoculture has deteriorated the physical as well as chemical fertility of the soils mainly due to depreciation of soil carbon. A study was undertaken in Shiwaliks region of northwest India to assess soil structural attributes under tree-based land uses viz., maize-wheat, agrohorticulture and agro-forestry (3 and 6-year plantation). The composite samples were collected from each cropping system at depth intervals of 0-15, 15-30, 30-60, 60-90 and 90-120 cm. The soils under agroforestry had significantly higher soil organic carbon (SOC) than in soils other land uses, (2.5 mg g-1) in 6- year and (2.1 mg g-1) in 3-year plantation. The mean bulk density was highest (1.57 Mg m-3) in soils under maize-wheat and lowest in agro-forestry 3-year soils (1.41 Mg m-3). The total porosity was lowest in maize-wheat (40.6%) soils as compared to other land uses. The mean weight diameter and water stable macro aggregates (>0.25 mm) were highest in soils under agro-forestry 6-year plantation than in soils under maize-wheat. On the other hand, water stable aggregates (< 0.25 mm) were lowest in soils under agro-forestry 6-year plantation than in soils under maize-wheat.